2006
DOI: 10.1002/jcc.20429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of liquid methanol and methanol–water mixtures with polarizable models

Abstract: A polarizable model for simulation of liquid methanol, compatible with the COS/G2 water model, has been developed using the Charge-on-Spring (COS) technique. The model consists of three point charges, with one polarizable center on the oxygen atom. The Lennard-Jones parameters on the oxygen atom together with the molecular polarizability were varied to reproduce the experimental heat of vaporization and density of liquid methanol at ambient conditions. We examined the energies of various methanol dimers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 74 publications
4
122
2
Order By: Relevance
“…The RDFs of methanol have been determined experimentally [8][9][10][11] and have been computed by means of full ab initio MD, 5,[12][13][14][15] mixed empirical and ab initio interactions 16,17 and force-fields. [18][19][20][21][22][23][24][25][26] Often, the first intermolecular peak in the RDF of methanol as well of water is overestimated compared to experiment. 12,13,[15][16][17][23][24][25][27][28][29][30] The search for plausible explanations of this quasi systematic overestimation forms the onset of a long debate, but until now it is not yet unraveled and what suits for one particular case does not suit for another case.…”
Section: 67mentioning
confidence: 99%
See 1 more Smart Citation
“…The RDFs of methanol have been determined experimentally [8][9][10][11] and have been computed by means of full ab initio MD, 5,[12][13][14][15] mixed empirical and ab initio interactions 16,17 and force-fields. [18][19][20][21][22][23][24][25][26] Often, the first intermolecular peak in the RDF of methanol as well of water is overestimated compared to experiment. 12,13,[15][16][17][23][24][25][27][28][29][30] The search for plausible explanations of this quasi systematic overestimation forms the onset of a long debate, but until now it is not yet unraveled and what suits for one particular case does not suit for another case.…”
Section: 67mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] Often, the first intermolecular peak in the RDF of methanol as well of water is overestimated compared to experiment. 12,13,[15][16][17][23][24][25][27][28][29][30] The search for plausible explanations of this quasi systematic overestimation forms the onset of a long debate, but until now it is not yet unraveled and what suits for one particular case does not suit for another case. When computing RDFs from molecular simulations based on first principles (e.g.…”
Section: 67mentioning
confidence: 99%
“…In other models parameters for hydroxyl groups are set to be unique for the particular alcohol being studied and can not be regarded as transferable across the alcohol series. [21][22][23] In the present work we extend these efforts via the development of a polarizable model for the alcohol series ( Figure 1) with emphasis on maximizing the transferability of the developed parameters to biological macromolecules. In addition, a systematic, iterative approach is applied to rigorously optimize all aspects of the force field parameters to maximize the overall accuracy of the model.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38]66 Furthermore, in two of these works 35,38 there was a comparison between the results produced by the potentials with and without polarization, indicating the need of polarization, even if some overstructuring could be occurring. 36,38 In the present model it is possible to turn off some molecular properties while keeping the same force field parameters, henceforth making the elucidation of the need of such property independent of a change in potential. Keeping the mobile charges fixed at certain positions would freeze a particular charge distribution, hence, for instance, its dipole, and then a nonpolarizable potential can be used.…”
Section: B Numerical Simulationsmentioning
confidence: 99%
“…Kashtanov et al 31 have suggested that numerical simulations could be using potentials that are not able to reproduce the hydrogen bonding network in ring structures. There is a substantial number of numerical simulations of methanol [18][19][20][21][22][23][32][33][34] and some of them which include polarizability [35][36][37][38] have shown the need for refined potentials.…”
Section: Introductionmentioning
confidence: 99%